Non-polynomial Spline Method for the Solution of Non-linear Burgers' Equation - Çağlar, Süleyman Hikmet; Uçar, Mehmet Fatih (Springer-Verlag Berlin, Heidelberger Platz 3, D-14197 Berlin, Germany, 2013)
A non-polynomial cubic spline method is proposed in this paper to solve one-dimensional non-linear Burgers' equation [Burger, A Mathematical Model Illustrating the Theory of Turbulence (1948); Rashidinia and Mohammadi, Int. J. Comp. Math. 85, 843-850 (2008)]. An example is solved to assess the accuracy of the method. The numerical results obtained by this way are compared with the exact solution to show the efficiency of the method.
Keywords: Mathematics; Matematik; Physics; Fizik; Finite-Element Approach; Numerical-Solution; Schemes; Time